2018
DOI: 10.1093/cvr/cvy033
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-specific deletion of Sirt1 gene sensitizes myocardium to ischaemia and reperfusion injury

Abstract: Cardiac SIRT1 mediates AMPK activation via LKB1 deacetylation, and AMPK modulates SIRT1 activity via regulation of NAD+ level during ischaemia. SIRT1 and AMPK agonists have therapeutic potential for treatment of aging-related ischemic heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
89
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 68 publications
(94 reference statements)
3
89
0
Order By: Relevance
“…AMPK, which acts as a conserved energy sensor, is the target of SIRT1 for regulation of cellular metabolism. Briefly, SIRT1 deacetylates LKB1, and then LKB1 is translocated from the nucleus to the cytoplasm, forms an active complex and activates AMPKα 25,33 . As metabolic sensors, SIRT1/AMPK signaling was shown to play important role in metabolism 33 .…”
Section: Discussionmentioning
confidence: 99%
“…AMPK, which acts as a conserved energy sensor, is the target of SIRT1 for regulation of cellular metabolism. Briefly, SIRT1 deacetylates LKB1, and then LKB1 is translocated from the nucleus to the cytoplasm, forms an active complex and activates AMPKα 25,33 . As metabolic sensors, SIRT1/AMPK signaling was shown to play important role in metabolism 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Dr Li's study clearly showed that the impaired AMPK activation in aged hearts was at least in part due to decreased SIRT1 activity. 4 Increased expression of SIRT1 via adenoviral transfection rescued the attenuation of AMPK activation and reduced ischaemic injury, providing key mechanistic support. Interestingly, they also found that there was a feedback interaction between AMPK and SIRT1 activation.…”
mentioning
confidence: 89%
“…3 Dr Li et al found that the substrate flexibility was markedly impaired in aged hearts following IR compared with young hearts. 4 They further found that the decreased substrate flexibility was due in part to impairment of the AMPK (AMP-activated protein kinase) signalling pathway activation. Glucose uptake and utilization was decreased in parallel with enhanced fatty acid oxidation.…”
mentioning
confidence: 99%
See 2 more Smart Citations